Discovery and study of abrasion behavior in granular shear flow. (22nd October 2022) - Hsiau, Shu-San; Hutter, Kolumban; Lu, Li-Shin; Teufel, Andreas; Chou, Shih-Hao; Sheng, Li-Tsung
ABSTRACT: Experiments were performed in an Couette ring shear cell with particles from the food industry of nearly spherical geometry and nominal diameters between 2.0 and 6.7 mm and with quartz grains with 2.1 to 3.3 mm diameter to examine whether rapid shear flow would give rise to an appreciable change in the granular properties. In particular, it was suspected that surface roughness would change during shearing and lead to changes in the values of the internal and wall friction angles. Measuring these angles corroborated the supposition that abrasion of the particles reduced their frictional resistance, both via the internal and wall friction angles. This demonstrates that roughness changes may occur in granular flows and should in those situations not be ignored in the theoretical descriptions.